The role of Lactobacillus in diseases and its intervention by Chinese herbs - Hui Lai; Dongmei Yan; Jiarong Zhang; Bin Li; Fei Li (Pharmacological Research - Modern Chinese Medicine, 2025)
Introduction: Lactobacilli are a group of Gram-positive bacteria belonging to the family Lactobacillaceae within the phylum Firmicutes. They colonize the intestinal tract and play a significant role in human health and disease treatment, serving irreplaceable functions in numerous disease domains. These include intestinal diseases (such as inflammatory bowel disease, diarrhea, colorectal cancer, etc.), viral respiratory infections, type 2 diabetes-related periodontitis, and urinary system diseases (prevention of vaginal diseases and urinary tract infections). Aim of the Review: This review focuses on the mechanisms of action of lactobacilli in diseases, the regulatory effects of diet and Chinese herbal medicine, and summarizes the impacts of Chinese herbal medicine on lactobacilli. It aims to explain the relationships among diseases, lactobacilli, and Chinese herbal medicine, providing theoretical support for promoting the research and development of related products. Methods: Literature related to lactobacilli was collected by searching the academic databases PubMed and CNKI using keywords such as characteristics of lactobacilli, biological functions, metabolic pathways, roles in diseases, mechanisms of action, and regulation by Chinese herbal medicine. Results: Based on the collected literature, this review summarizes the characteristics, biological functions, metabolic pathways, roles in diseases, and mechanisms of action of lactobacilli, as well as the regulatory effects of diet, single Chinese herbal medicines, and Chinese herbal compound formulas on the abundance of lactobacilli. Discussion: Dietary and Chinese herbal medicine interventions significantly influence the growth and reproduction of intestinal lactobacilli. A high-protein diet and specific carbohydrates can regulate lactobacilli levels, but their specific mechanisms of action remain unclear. The molecular-level interactions with host cells and the signaling pathways under different disease states are not yet fully understood. Future research could deeply analyze the molecular-level interactions between lactobacilli and host cells, clarify the key signaling pathways activated or inhibited under different disease conditions, and provide a theoretical basis for precision treatment.